Assessment of Gene Flow Between Gossypium hirsutum and G. herbaceum: Evidence of Unreduced Gametes in the Diploid Progenitor. Issue 7 (1st July 2017) - Montes, E; Coriton, O; Eber, F; Huteau, V; Lacape, J M; Reinhardt, C; Marais, D; Hofs, J L; Chèvre, A M; Pannetier, C
Abstract: In the framework of a gene flow assessment, we investigated the natural hybridization rate between Gossypium hirsutum (AADD genome) and G. herbaceum (AA genome). The latter species, a diploid progenitor of G. hirsutum, is spontaneously present in South Africa. Reciprocal crosses were performed without emasculation between G. herbaceum and G. hirsutum . Neither examination of the morphological characteristics nor flow cytometry analysis of the 335 plants resulting from the G. hirsutum × G. herbaceum cross showed any hybrid features. Of the 148 plants produced from the G. herbaceum × G. hirsutum cross, three showed a hybrid phenotype, and their hybrid status was confirmed by SSR markers. Analysis of DNA content by flow cytometry and morphological traits clearly showed that two of these plants were triploid (AAD). The third plant had a flow cytometry DNA content slightly higher than G. hirsutum . In addition, its morphological characteristics (plant architecture, presence and size of petal spots, leaf shape) led us to conclude that this plant was AAAD thus resulting from fertilization with an unreduced AA gamete of the female G. herbaceum parent. Fluorescent In Situ Hybridization (FISH) and meiotic behavior confirmed this hypothesis. To the best of our knowledge, this is the first description of such gametes in G. herbaceum, and it opens new avenues in breeding programs. Furthermore, this plant material could provide a useful tool for studying the expression of genes duplicated in the A and D cotton genome.